The Effect Of Halal Labeling On The Decision To Purchase Toothpaste Products For Unissula Students - Amalia, Khofifah; Amurwaningsih, Musri; Sunnah, Tahta Danifatis (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Toothpaste is a dental and oral hygiene ingredient that is used every day by the community. The era of modernization has caused toothpaste products to be sold freely in the market. The halal labeling is useful for knowing that toothpaste is halal and safe in accordance with Islamic law. The purpose of this study was to determine the effect of halal labeling on purchasing decisions for toothpaste products for UNISSULA students.Method: This research is a non-experimental observational analytic study with a quantitative approach. The research subjects were taken using a cluster sampling technique based on the faculties in UNISSULA. The data were analyzed using Spearman correlation analysis and descriptive analysis.Result: The results of the Spearman correlation test showed a significant difference with p = 0.00 (p <0.05) with a strong correlation strength of 0.616 and a positive correlation direction.Conclusion: Halal labeling influences the decision to buy toothpaste for UNISSULA students with high levels of perception of halal labeling and high and medium halal labeled toothpaste purchasing decisions.